The role of stigma in the design of welfare programs - Tomer Blumkin; Yoram Margalioth; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2008)
We consider the notion of welfare stigma à la Besley and Coate (1992b). This stigma is attributed to welfare claimants by society when they are perceived as undeserving in the sense that they falsely claim to be eligible for welfare benefits. However, due to imperfect information, this stigma may be extended, with some probability, to all welfare claimants. We examine the implications of this kind of stigma for the design of welfare programs.
Keywords: H2; D6; 330; welfare; take up; targeting; inequality; stigma; Sozialpolitik; Sozialhilfeempfänger; Soziale Ungleichheit; Theorie